A UTILIZAÇÃO DA BANANA COMO FONTE DE RENDA PARA PEQUENOS PRODUTORES - Cristina da Silva Barros, Erlaine; Antônio Inácio, Reinaldo; Oliveira Pinto, Fernanda; da Silva Quintas, Edleuza; Diego Rodrigues, Marlon (LINKSCIENCEPLACE, 2026)
Banana is the fourth most produced food product on the planet , preceded by rice, wheat and corn. This result is grown in more than 107 countries; from tropical regions as the world’s subtropical, in an area of 4.1 million hectares and production of 95 million tons, the second most widely produced fruit in the world. The banana is grown in all states of Brazil, occupying an area of 492,113,000 hectares and an estimated production of approximately 7.1 million tons. Brazil has a very diverse profile of production compared to the technological level adopted. The production ranges from small highly technical farmers, small farmers without adopting planting technology and management and have other cultures as an economic base. This work has as main objective report that the Banana Pacovan Silver is not only a food, but assists as a source of income for small farmers. And as specific objectives show the various forms of use and exploitation of banana from its pulp to your straw; verify Banana interaction with other cultures; analyze the culture of installation on small farms; show that the Banana Silver Pacovan is present in the diet of Brazilians, regardless of their income . This study is justified by the need to show how the banana can be an alternative for the generation of income for small farmers. The main question of this study was to determine whether it would be possible to banana production on small farms; source of income, in addition to proper management, reuse of plant structures for fertilizers (leaves, pseudostem, etc.) and the Banana interaction with other cultures. An applied research of exploratory, explanatory, experimental was initially performed. The research was initiated through literature searches with authors dealing with the subject. Were prioritized searches in scientific articles, books, monographs, dissertations, journals, websites, and other documents. After bibliographic research was carried out in a second step an interview, containing 10 questions such structured and open with the responsible owner (micro-entrepreneur) by banana production from the property. Through this study it can be said that you can use the banana culture to help source of income for small farmers.